2009
DOI: 10.1002/fuce.200800144
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and Microfabrication Considerations for Self‐Supported On‐Chip Ultra‐Thin Micro‐Solid Oxide Fuel Cell Membranes

Abstract: La0.6Sr0.4Co0.8Fe0.2O3 – δ (LSCF) has been sputtered on bare Si and Si3N4 and yttria‐stabilised zirconia (YSZ) thin films to investigate annealing temperature‐ and thickness‐dependent microstructure and functional properties, as well as their implications for designing failure‐resistant micro‐solid oxide fuel cell (μSOFC) membranes. The LSCF thin films crystallise in the 400–450 °C range; however, after annealing in the 600–700 °C range, cracks are observed. The formation of cracks is also thickness‐dependent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…Our recent study on crack formation in fuel cell electrode films [39] has revealed that rather than shrinkage during sintering, or differential contraction during cooling as reported in many studies [40,41], the critical factor for obtaining crack-free and smooth films in this study was the ability of the ink to be self-leveling in the earlier wet state. Cracking was initiated at the drying stage if the particles were prevented from packing more effectively as the liquid was removed.…”
Section: Crack Elimination and Surface Quality Improvement For Lscf64mentioning
confidence: 59%
“…Our recent study on crack formation in fuel cell electrode films [39] has revealed that rather than shrinkage during sintering, or differential contraction during cooling as reported in many studies [40,41], the critical factor for obtaining crack-free and smooth films in this study was the ability of the ink to be self-leveling in the earlier wet state. Cracking was initiated at the drying stage if the particles were prevented from packing more effectively as the liquid was removed.…”
Section: Crack Elimination and Surface Quality Improvement For Lscf64mentioning
confidence: 59%
“…Detailed fabrication design and procedures are discussed elsewhere. 37,38 For fuel cell measurements on methane, room temperature humidified pure methane gas was fed at a flow rate of 200 ml min À1 to the anodes of mSOFCs from the bottom of the chips. For hydrogen fuel cell measurements, room temperature humidified 5% hydrogen/Ar balanced gas was supplied at a flow rate of 100 ml min À1 .…”
Section: Thin Film Msofc Fabrication and Measurements With Ru Anodesmentioning
confidence: 99%
“…As can be seen in Table 2, the surface roughness for the films made from 1:2 ink was reduced to merely 10% that of films made from the as-receivedink.This is much smaller than the indentation depth, resulting in a steep reductionin the relative standard deviationofmeasured elastic modulus from 63.2% to 6.2%. The experiments above revealed that rather than shrinkage during sintering, or differential contraction during cooling as proposed in many studies [11,17], the more critical factor for obtaining crack-free and flat films in the current study was the ability of the ink to be self-leveling in the early wet state. Cracking is most likely to initiate at the drying stage if the particles are prevented from packing more effectively as the liquid content was removed.…”
Section: Fig 15 (A) High Magnification Surface and (B)mentioning
confidence: 51%